Analisis Kestabilan Lereng Disposal Dengan Menggunakan Metode Bishop Di Site Puncak Jaya CV. Tekad Jaya Lareh Sago Halaban Kabupaten Lima Puluh Kota - Nadilla Putri; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2021)
CV. Tekad Jaya has a Production Operation Mining Business Permit (IUP) for limestone excavation on an area of 6.5 hectares located in Jorong Bulakan, Nagari Tanjung Gadang, Lareh Sago Halaban District, Limapuluh Kota Regency, West Sumatra Province. On CV. Tekad Jaya there is an avalanche that occurs on the slopes of the disposal heap. The avalanche is assumed to be an arc avalanche with the initial slope geometry before the avalanche is 72o and a height of 44 meters. The landslide resulted in disruption of production activities due to the position of the disposal area being above the production area. To avoid landslides in the future and to get the ideal slope geometry, a thorough geotechnical study is needed and what method will be used. Based on the results of research and analysis conducted at the research location, the value of geotechnical parameters after the parameters of the physical and mechanical properties of the slope material were tested, namely the natural bulk weight of 11,94 kN/m3, the dry weight of 10,24 kN/m3, and the saturated weight of 13,48 kN/m3. While the cohesion value is 52.147 kN/m3, and the internal shear angle is 24.45o. The FK value based on the parameter values of the physical-mechanical properties of soil samples in the laboratory is the slope safety factor value in dry conditions is 1.171 and in saturated conditions is 1.002. The results of the study obtained that the safety factor (SF) value of the overall slope geometry recommendation with a slope height of  44 meters and a slope angle of 48o for dry conditions according to the Bishop Simplified method was 1,49, while according to the Hoek and Bray method was 1,89. And for the saturated condition, the safety factor (SF) value obtained according to the Bishop Simplified method is 1.304, while according to the Hoek and Bray method, it is 1.19.